Mitigasi Bencana Dalam Peningkatan Kewaspadaan Terhadap Ancaman Gempa Bumi Di Universitas Andalas - Nursyabani Nursyabani; Roni Ekha Putera; Kusdarini Kusdarini (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2020)
This study aims to describe and analyze how the implementation and process of earthquake disaster mitigation at Universitas Andalas. This research was motivated by the high risk of earthquake disasters at Universitas Andalas and the still low education and understanding of students and academic aspirations of disaster mitigation. So it is necessary to optimize mitigation activities in the Universitas Andalas campus area. This is in accordance with Law Number 24 of 2007 concerning Disaster Management and the Tridarma of Higher Education which has a strategic role in disaster management, especially in relation to learning, research and community service. The method used in this research is descriptive qualitative, data collection techniques using interviews and documentation. To test the authenticity of the data obtained in the field, researchers used source triangulation techniques. The selection of informants was done by purposive sampling. As for the results of this study, in general, disaster mitigation activities in increasing awareness of the threat of an earthquake in Universitas Andalas have not run optimally. This is evidenced by the implementation of several activities that failed to achieve the target in the form of increased disaster alertness and increased understanding of students and academics on disaster mitigation, the absence of regulations containing the implementation of disaster mitigation activities at Universitas Andalas. Lack of involvement of external organizations in implementing disaster mitigation activities, as well as limited human resources and budget in implementing disaster mitigation activities. The results showed that the alternative policy was chosen based on the criteria for selecting the alternative policy: 1) Technical feasibility, it was found that the purpose of establishing KEK was as a forum for ecraf’s actors. 2) Economic and financial, KEK doesn’t receive any special funds and no goals have been achieved. 3) Political viability, this policy doesn’t contradicting with the applicable regulations. 4) Administrative Operability policy is realistic, but the support from the nine offices has not been maximal. 5) The criteria chosen are based on the success of the other regions and then it is adopted. It is the main criteria in the process of selecting and determining KEK as an alternative policy for the development of creative economy potentian in Banyumas Regency